Tax Treaty Shopping in Ethiopia: The Need to Integrate Anti-Treaty Shopping Rule into Double Taxation Avoidance Agreements and domestic income tax law. - Alemu Balcha Adugna, Alemu Balcha (Bahir Dar University Journal of Law, 2022)
Many countries of the world have signed bilateral tax treaties to avoid or mitigate double taxation and control tax evasion and planning in cross-border economic activities. However, such networks of bilateral tax treaties have in effect opened room for tax treaty shopping. As of September 2020, Ethiopia has signed more than 32 bilateral tax treaties. Yet, no study has been made on the issues of tax treaty shopping. Hence, this study examines whether the existing treaty provisions are sufficient to prevent the abuse of double taxation agreements by treaty shopping, and identifies its shortcomings. To this end, doctrinal legal research methodology is employed to investigate Ethiopia's pertinent income tax law and double taxation avoidance agreements. Accordingly, the findings show that tax treaty shopping is not sufficiently regulated under the Ethiopian bilateral tax treaties and domestic income tax system. Most of the Ethiopian bilateral tax treaties are devoid of anti-treaty shopping rules. Save for few bilateral tax treaties, most of the bilateral tax treaties have no anti-treaty shopping rules. Although the Federal Income Tax Proclamation has provided seemingly anti-avoidance rule, it may not serve its purposes since it cannot override treaties which may otherwise constitute a breach of the treaty under international law. In other words, the general anti-avoidance rule provided under the Federal Income Tax Proclamation may not extend to tackling treaty shopping as its scope is limited to domestic matters. Accordingly, Ethiopia should revisit its domestic anti-avoidance rules and incorporate anti-treaty shopping rules into bilateral tax treaties either by renegotiation or termination.